Comparative Proteome-Wide Abundance Profiling of Yeast Strains Deleted for Cdc48 Adaptors - Valentina Rossio; Joao A. Paulo (Proteomes)
The yeast ATPase Cdc48 (known as p97/VCP in human cells) plays an important role in the Ubiquitin Proteasome System. VCP is essential for cancer cell proliferation, and its dysregulation has been implicated in several neurodegenerative diseases. Cdc48 functions by extracting ubiquitylated proteins from membranes, protein complexes and chromatin by often facilitating their proteasomal degradation. Specific adaptors or cofactors, primarily belonging to the UBX domain-containing protein family (which has seven members in Saccharomyces cerevisiae) recruit Cdc48 to ubiquitylated proteins. Here, we employed sample multiplexing-based quantitative mass spectrometry to profile global protein abundance in p97 adaptor deletion strains, specifically comparing seven single deletion strains of UBX domain-containing proteins and the Cuz1 deletion strain, which belongs to the zinc finger AN1-type domain protein family. We observed that each strain showed unique sets of differentially abundant proteins compared to the wild type. Our analysis also revealed a role for Ubx3 in maintaining wild type levels of mitochondrial proteins. Overall, we identified ~1400 differentially abundant proteins in the absence of a specific Cdc48 adaptor. This unique dataset offers a valuable resource for studying the functions of these adaptors, aiming to achieve a better understanding of the cellular processes regulated by Cdc48 itself and to deepen our understanding of the Ubiquitin Proteasome System.